2021
DOI: 10.1155/2021/5559884
|View full text |Cite
|
Sign up to set email alerts
|

Selected Quality Attributes of Wheat Flour Added with Overozonized Wheat Flour

Abstract: Overozonized wheat flour was added to unozonized wheat flour at three different ratios (M1: 1 : 1; M2: 1 : 2; and M3: 1 : 3), and the mixed flour was evaluated for quality properties, including pH, protein component, dough property, pasting property, and steamed bread quality. The pH of the mixed flour gradually increased as the addition content of overozonized flour decreased. The three mixed flour had higher insoluble polymeric protein (IPP) content than unozonized flour. Compared with overozonized flour, M1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Ozone treatments of wheat flours were conducted in a Büchner flask (2500 mL). For high-intensity ozone treatment, ozone gas was generated by a HW-ET ozone generator (Guangzhou Huanwei Environment Protection Science and Technology Co., Ltd., Jinan, China) with an ozone flow rate of 3.82 g/h [16]. For low-intensity ozone treatment, ozone gas was generated by a FL-803A ozone generator (Shenzhen Feili Electronic Appliance Technology Co., Ltd.) with an ozone flow rate of 0.61 g/h.…”
Section: Ozone Treatment Of Wheatmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozone treatments of wheat flours were conducted in a Büchner flask (2500 mL). For high-intensity ozone treatment, ozone gas was generated by a HW-ET ozone generator (Guangzhou Huanwei Environment Protection Science and Technology Co., Ltd., Jinan, China) with an ozone flow rate of 3.82 g/h [16]. For low-intensity ozone treatment, ozone gas was generated by a FL-803A ozone generator (Shenzhen Feili Electronic Appliance Technology Co., Ltd.) with an ozone flow rate of 0.61 g/h.…”
Section: Ozone Treatment Of Wheatmentioning
confidence: 99%
“…McDonough et al [6] found that exposing adults of Sitophilus oryzae to 1800 ppm ozone for 60 min can achieve 100% mortality. Wu et al [7] reported that treating wheat grains (50 g) with 16.5 mg/min ozone for 5 min inactivated 96.9% of the fungal spores. e biocidal activity of ozone is based essentially on its powerful oxidizing capacity, which arouses irreversible change to unsaturated fatty acids of cell membrane and cellular macromolecules, for example, DNA and proteins [8,9].…”
Section: Introductionmentioning
confidence: 99%